2021
DOI: 10.1108/et-03-2021-0118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of role model teachers on students' entrepreneurial competencies and intentions

Abstract: PurposeThe paper aims to provide empirical evidence on whether the identification of the teacher as a role model is truly a key factor in improving students' entrepreneurial competencies and intention.Design/methodology/approachData were obtained from a survey of 387 university students enrolled in an entrepreneurship course, who were asked to respond to the same questionnaire at the beginning and at the end of the semester. To test the proposed hypotheses, comparison of means tests for independent samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
3
8
0
Order By: Relevance
“…Entrepreneurial desire is the antecedent of an individual's entrepreneurial intention (Shapero and Sokol, 1982;Peterman and Kennedy, 2003). Entrepreneurial role models have significant positive association with entrepreneurial intention (Fellnhofer, 2017b;Fellnhofer and Mueller, 2018;Van Trang et al, 2019;San-Martin et al, 2021). Therefore, the previous studies are aligned with the results of the current study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Entrepreneurial desire is the antecedent of an individual's entrepreneurial intention (Shapero and Sokol, 1982;Peterman and Kennedy, 2003). Entrepreneurial role models have significant positive association with entrepreneurial intention (Fellnhofer, 2017b;Fellnhofer and Mueller, 2018;Van Trang et al, 2019;San-Martin et al, 2021). Therefore, the previous studies are aligned with the results of the current study.…”
Section: Discussionsupporting
confidence: 85%
“…The previous studies have showed that entrepreneurial role models have Entrepreneurial hands-on practice as a moderator between entrepreneurial perceived behavioral control and entrepreneurial calling. significant positive association with entrepreneurial perceived behavioral control (Fellnhofer, 2017b;Fellnhofer and Mueller, 2018;Van Trang et al, 2019;San-Martin et al, 2021), and its similar variables, including entrepreneurial competence (Van Trang et al, 2019), and entrepreneurial perceived feasibility (Zozimo et al, 2017). Entrepreneurial perceived behavioral control is positively associated with entrepreneurial intention (Chien-Chi et al, 2020;Huang and Zhang, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for implementing entrepreneurship learning in schools is much influenced by the teacher's awareness of the importance of practice, not just theory, and the readiness of these teachers to take part in the training (Ratten & Jones, 2021;San-Martín et al, 2022). These factors influence the success of the implementation of entrepreneurship learning.…”
Section: Resultsmentioning
confidence: 99%
“…According to [69], teachers who set an example for students see a significant rise in students' ECs and perceived behavioral controls throughout the semester; however, their attitude toward intention decreases. ECs and EM are significant predictors of SMEs' performances in Nigeria's Benue State [70].…”
Section: Entrepreneurial Competencies (Ecs) and Entrepreneurial Minds...mentioning
confidence: 99%